Combined assessment of thrombotic and haemorrhagic risk in acute medical patients - Regina, Micaela La; Orlandini, Francesco; Marchini, Francesca; Marinaro, Alessia; Bonacci, Rosanna; Bonanni, Paola; Corsini, Francesca; Ceraudo, Anna Maria; Pacetti, Edoarda; Scuotri, Lucia; Costabile, Davide; Dentali, Francesco (Thrombosis and Haemostasis, 2016)
Acute medical patients have a high risk of venous thromboembolic events (VTE). Unfortunately, the fear of bleeding complications limits the use of antithrombotic prophylaxis in this setting. To stratify the VTE and haemorrhagic risk, two clinical scores (PADUA, IMPROVE) have recently been developed. However, it is not clear how many patients have a concomitant high VTE and haemorrhagic risk and what is the use of prophylaxis in this situation. To clarify these issues we performed a prospective cohort study enrolling consecutive patients admitted to internal medicine. Patients admitted to internal medicine (January to December 2013) were included. VTE and haemorrhagic risk were evaluated in all the included patients. Use and type of anti-thrombotic prophylaxis was recorded. A total of 1761 patients (mean age 77.6 years) were enrolled; 76.8 % (95 % CI 74.7–78.7) were at high VTE risk and 11.9 % (95 % CI 10.4–13.5) were at high haemorrhagic risk. Anti-thrombotic prophylaxis was used in 80.5 % of patients at high VTE risk and in 6.5 % at low VTE risk (p< 0.001), and in 16.6 % at high haemorrhagic risk and in 72.5 % at low haemorrhagic risk (p< 0.001). Prophylaxis was used in 20.4 % at both high VTE and haemorrhagic risk and in 88.9 % at high VTE risk but low haemor-rhagic risk. At multivariate-analysis, use of prophylaxis appeared highly influenced by the VTE risk (OR 68.2, 95 % CI 43.1 - 108.0). In conclusion, many patients admitted to internal medicine were at high risk of VTE. Since almost 90 % of them were at low haemorrhagic risk, pharmacological prophylaxis may be safely prescribed in most of these patients.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Anticoagulants; internal medicine; haemorrhage; prophylaxis; venous thromboembolism